Linguistic Ambiguity Between Ibn Hisham and Chomsky - عواودة, فاتنة; مراشدة, رائدة; بني بكر, عبد القادر (Jadara Journal of Social Sciences, 2025)
The aim of this research is to study the linguistic ambiguity between the grammarian Ibn Hisham (d. 761 AH) and the contemporary American linguist Chomsky, whose fame has spread, and whose name is associated with the generative transformational theory, considered by many as a significant discovery in the field of contemporary linguistics. The research addressed the following issues: 1- Ambiguity in language and terminology. 2 Ambiguity according to Ibn Hisham. 3- Ambiguity according to Chomsky. 4- Comparison between Ibn Hisham's and Chomsky's views on ambiguity. In this study, the researcher adopted the descriptive-analytical approach, which is based on analyzing the scholars’ views on linguistic ambiguity, and explaining its cause and manifestations through their works and what has been written about them. The research concluded that Ibn Hisham was proactive in understanding linguistic ambiguity and its causes in Arabic, indicating that ambiguity occurs due to phonetic, morphological, syntactic, or semantic reasons, leading to the multiplicity of meanings in linguistic structures and consequently to the multiplicity of parsing in a single structure. As for Chomsky, ambiguity is semantic, caused by linguistic structure ambiguity, where a structure has two or more meanings, or where the structure is grammatically correct but it is meaningless semantically. Keywords: Ambiguity, generative, transformational, Ibn Hisham, Chomsky